Gobak sodor Games in Building Student Character Through Physical Education Lessons Sports Health - Luthfiani LU’LU’IL Mantsuro; Endang Sri Hanani; Donny Wira Yudha Kusuma (Journal of Physical Education and Sports, 2022)
Character education is necessary for understanding values as a way of thinking and behaving well toward oneself, family, and the environment, particularly for middle school students. This study aims to investigate the impact of gobak sodor on the character development of junior high school students in the Weru Cirebon District. This research methodology is qualitative. This study used school principals, PE teachers, and junior high school students from Weru District, Cirebon Province, as data sources. Among the methods of data collection are observation, interviews, and documentation. The data validation technique is source and technique triangulation. The obtained data was qualitatively analyzed using the following steps: (1) data collection; (2) data reduction; (3) data presentation; and (4) conclusion drawing. This study's findings are the gobak sodor game with religious value indicators. Among the 86 respondents, 45 percent (39 students) said they always pray before starting to study. The democratic value indicator is 67.4% of all respondents who always hold democratic discussions in the playgroup selection process. The value indicator for students appreciating the performance on aspects where they do not mock the losing team is 38.4% with a Yes answer. Conclude that playing the traditional gobak sodor game may contribute to the character development of junior high school students in the Weru District of the Cirebon Regency.